Total Flavones of Abelmoschus manihot Ameliorates Podocyte Pyroptosis and Injury in High Glucose Conditions by Targeting METTL3-Dependent m6A Modification-Mediated NLRP3-Inflammasome Activation and PTEN/PI3K/Akt Signaling - Liu, Bu-Hui; Tu, Yue; Ni, Guang-Xia; Yan, Jin; Yue, Liang; Li, Zi-Lin; Wu, Jing-Jing; Cao, Yu-Ting; Wan, Zi-Yue; Sun, Wei; Wan, Yi-Gang (Frontiers in Pharmacology, 2021)
Background: The total flavones of Abelmoschus manihot (TFA), a compound that is extracted from Abelmoschus manihot, has been widely used in China to reduce podocyte injury in diabetic kidney disease (DKD). However, the mechanisms underlying the therapeutic action of this compound have yet to be elucidated. Podocyte pyroptosis is characterized by activation of the NLRP3 inflammasome and plays an important role in inflammation-mediated diabetic kidneys. Regulation of the PTEN/PI3K/Akt pathway is an effective strategy for improving podocyte damage in DKD. Previous research has also shown that N6-methyladenosine (m6A) modification is involved in DKD and that m6A-modified PTEN regulates the PI3K/Akt pathway. In this study, we investigated whether TFA alleviates podocyte pyroptosis and injury by targeting m6A modification-mediated NLRP3-inflammasome activation and PTEN/PI3K/Akt signaling. Methods: We used MPC-5 cells under high glucose (HG) conditions to investigate the key molecules that are involved in podocyte pyroptosis and injury, including activation of the NLRP3 inflammasome and the PTEN/PI3K/Akt pathway. We detected alterations in the levels of three methyltransferases that are involved in m6A modification. We also investigated changes in the levels of these key molecules in podocytes that overexpressed or knockdown methyltransferase‑like (METTL)3. Results: Analysis showed that TFA and MCC950 protected podocytes against HG-induced pyroptosis and injury by reducing the protein expression levels of gasdermin D, interleukin-1β, and interleukin-18, and by increasing the protein expression levels of nephrin, ZO-1, WT1 and podocalyxin. TFA and 740Y-P inhibited activation of the NLRP3 inflammasome via the PI3K/Akt pathway by inhibiting the protein levels of NIMA-related kinase7, NLRP3, ASC, and caspase-1, and by increasing the protein expression levels of p-PI3K and p-Akt. TFA improved pyroptosis and injury in HG-stimulated podocytes by regulating METTL3-dependent m6A modification. Conclusion: Collectively, our data indicated that TFA could ameliorate pyroptosis and injury in podocytes under HG conditions by adjusting METTL3-dependent m6A modification and regulating NLRP3-inflammasome activation and PTEN/PI3K/Akt signaling. This study provides a better understanding of how TFA can protect podocytes in DKD.